The influence of media on the voting behaviour among the Semai Orang Asli at the 14th General Election in Malaysia / Nurmalis Musa and Ismail Sualman - Musa, Nurmalis; Sualman, Ismail (Centre for Media and Information Warfare Studies, 2020)
Ethnic and religious communalism in large part define the Malaysian political landscape. The 14th General Election (GE14) witnessed a drastic swing in the support of the Bumiputera ethnic voters from Barisan Nasional to Pakatan Harapan. Dissatisfaction with the rising cost of living, voters' increasing awareness of electoral issues and influence of mainstream and social media - all impacted their voting behaviour. This study applies the quantitative method and aims to examine the influence of media on the voting behaviour among the Orang Asli Semai electorate who lives in Batang Padang, Perak, specifically in the polling district of Parliament Tapah, P072 in the Perak State Legislative Assembly constituency of Chenderiang (DUN Chenderiang). Information is gleaned from post-GE14 findings as well as from the experience at previous elections. The research objectives are to identify the media preferences of the Orang Asli Semai electorate and to determine the contributing factors that influence their voting behaviour. A multiple regression test that was used to identify the contributing factors of media instruments' influence on voting behaviour had determined that although the influence of the media is not so major, it nevertheless was a contributing factor that influences voting behaviour among the Orang Asli Semai as agents to deliver and disseminate information regarding social imagery, current events, and issues and policies. The findings can contribute to the improvement of political engagement between political leaders and voters from the indigenous groups which can be used as a political strategy in future elections.